IMPROVING THE MECHANISM OF INTERACTION BETWEEN THE COMPONENTS OF THE SECURITY AND DEFENSE SECTOR IN RESPONDING TO THREATS TO SOCIO-POLITICAL STABILITY - Balan , Mykola (Theory and Practice of Public Administration, 2019)
A major obstacle to the development of Ukrainian society is the threat to socio-political stability, which now constantly occur and causes a crisis in the development of state formation. The inefficient practice of managing recent crisis events shows that the issues of organizing the interaction of public policy entities under these conditions require special attention and study. Therefore, the implementation of state policy on improving the mechanism of interaction between the components of the security and defense sector is an extremely relevant research area. The purpose of the article is to investigate the nature of the state response to threats to socio-political stability and improve the mechanism of interaction between the components of the security and defense sector under these conditions. The article establishes that the main components of the security and defense sector of Ukraine that respond to threats to socio-political stability are the bodies and units of the National Police of Ukraine, bodies and units of the Security Service of Ukraine, military units and subunits of the National Guard of Ukraine, bodies and units of the State Border Service of Ukraine, bodies and divisions of the State Security Service of Ukraine. Military formations and special-purpose law enforcement agencies, as the main subjects of ensuring national security of Ukraine, constantly perform compatible tasks under the conditions of threats to socio-political stability. The organization of interagency interaction of the components of the security and defense sector under the conditions of threats to socio-political stability is usually understood as a set of interrelated measures to coordinate and synchronize joint actions for the purpose, task, place, time and methods of performing military-combat tasks, ensuring military and combat tasks, society and the state. The structure of the mechanism of interaction between the components of the security and defense sector that responds to threats to socio-political stability is developed in the article. The developed structure aims to structure the order of organization of interaction between the components of the security and defense sector at the highest, central and territorial levels of public administration. Special in the substantiated structure belongs to the bodies of organization of interaction at the specified levels. The areas of further scientific exploration will focus on improving the forms and methods of responding to the security and defense components of threats to socio-political stability.